FLASH DISSOLVING SUBLINGUAL ALMOTRIPTAN MALATE LYOTABS FOR MANAGEMENT OF MIGRAINE - Kassem, Abeer Ahmed; Labib, Gihan Salah (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Development of sublingual fast dissolving lyophilized almotriptan tablets, to enhance its pre-gastric absorption and so alleviating the gastrointestinal dysmotility that is commonly associated with migraineurs. Methods: Primary almotriptan lyophilized tablets (Alm-lyotab), were prepared using polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), gelatin, or sodium alginate, as a bulk forming agent and mannitol as a disintegrant, cryoprotectant and taste improver. Physical properties, wetting time, in vitro dissolution and disintegration behaviour, were investigated. A combination of PVP, gelatin and chitosan in different ratios with mannitol were developed and characterised for further improvement. Optimised formula was examined by scanning electron microscope (SEM), differential scanning calorimetry (DSC) and Fourier-transform infrared spectroscopy (FTIR). Results: Both PVP and gelatin primary formulations showed elegant appearance with fast in vitro disintegration time of 5.67 and 5.64 sec, short wetting time of 4.06 and 4.05 sec, respectively, and high in vitro release rate of about 80% after 1 min, thus they were selected for further improvement. Optimised formula from polymer blend formulations (F8) which consisted of PVP: gelatin: chitosan in a ratio of its constituting solutions of 1:5:0.5, exhibited an elegant appearance, drug content of 98.75 %, in vivo disintegration time of 1.85 sec and complete drug release within 1 min. SEM micrographs revealed spongy, highly porous structure. DSC results indicated the presence of the drug in its crystalline form. FTIR studies revealed no interaction between the drug and excipients. Conclusion: Sublingual instantly dissolving Almo-lyotab was successfully developed and may constitute an advance in the management of acute migraine attacks.